2022
DOI: 10.3390/economies10100242
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Green Banks and Stock Return Volatility: GLE Algorithm and Neural Network Models

Abstract: This study investigates the effects of ESG factors on stock return volatility from 2012 to 2020 using linear regression, GLE algorithm, and neural network models. This paper used the ESG factors and main control variables (ROA, EPS, and year) as independent variables. The regression model results showed that both year and E scores significantly positively affected Saudi banks’ stock return volatility. However, the S score and ROA significantly negatively impacted the volatility. The results indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Laokulrach (2022) also found that companies that implement ESG in 7 out of 8 industries have higher stock volatility than the industry average. Several other studies also attempted to examine further the influence of ESG on stock volatility based on each of its components, namely E, S, G and found that there was a positive, negative, or insignificant influences of each component on stock volatility (Assous, 2022;Meher et al, 2020;Yoo et al, 2021).…”
Section: Introduction *mentioning
confidence: 99%
“…Laokulrach (2022) also found that companies that implement ESG in 7 out of 8 industries have higher stock volatility than the industry average. Several other studies also attempted to examine further the influence of ESG on stock volatility based on each of its components, namely E, S, G and found that there was a positive, negative, or insignificant influences of each component on stock volatility (Assous, 2022;Meher et al, 2020;Yoo et al, 2021).…”
Section: Introduction *mentioning
confidence: 99%